Effect of freeze-thaw cycles on shear strength of unsaturated bentonite modified clay - Jing, Xin; Cui, ZiZhi; Doh, Shu Ing; Ma, Li; Wei, Lu (Elsevier, 2021)
Freeze–thaw cycles is a seasonal process which occurs in many north regions of soils. Understanding the effects of freeze–thaw cycle on the physico-mechanical behaviours of soils is critical for construction stabilisation and reduce the freeze-thaw damage of foundation engineering. Over the years, studies has been conducted to investigate the effect of freeze-thaw cycles to the periodic strength characteristics of clay. Additive reinforced materials are used to reduce the damages which caused by freeze-thaw cycles and has made series significant contribution to foundation engineering. In this study, bentonite would be added as an additive to investigate the strength characteristics of unsaturated bentonite modified clay after different freeze–thaw cycles. Specimens of natural clay were mixed with different saturation, dry density and bentonite content. The results indicated that dry density, saturation and bentonite content give significant effect on shear strength of bentonite modified clay after freeze–thaw cycles. Meanwhile, the cohesion and internal friction angle of soils gradually attenuated with the increase of dry density, freeze–thaw cycles and saturation. It is found that during the freeze–thaw cycles, the reduction of internal friction angle and cohesion is most obvious at the first freeze-thaw cycle, and gradually stabilized after 7th freeze-thaw cycle. Moreover, results shown that the content of bentonite can effectively improve the cohesion, and maintain positive effects to the internal friction angle. Therefore, appropriate content of bentonite can effectively improve the freeze-thaw resistance of clay.